The Trouble with Inversion: An examination of science and sexual orientation - Johnston, Rebekah (Les ateliers de l'éthique / The Ethics Forum)

(untitled) (Centre de recherche en éthique de l’Université de Montréal, 2008)
Although some are excited about the possibility of using current scientific research into the biological causes of sexual orientation to ground rights claims, I argue that basing rights claims on this research is unwise because this research, specifically the hormonal, genetic, and structural research, is organized around the inversion assumption, a conceptual scheme within which some aspect of the biology of gay men and lesbians is thought to be inverted along sex lines. While there are many reasons to worry about the use of the inversion assumption, I focus on problems that arise from a further set of claims that must be assumed in order to make the use of the inversion assumption coherent. This further set of assumptions includes the claims (1) that heterosexuality is the standard state and that (2) this standard state is sexually-dimorphic and (3) deterministic. I argue that this set of assumptions is problematic because it results in ideological consequences that are both sexist and heterosexist.